External Ventricular Drainage Reduces Mortality in Spontaneous Intraventricular Hemorrhage of Brain: A Comparative Study (Bangladesh Journal of Neurosurgery, 2022)
Introduction: External ventricular drain (EVD) usage in patients with intraventricular hemorrhage (IVH) is variable in current practice and clinical trials, and its impact on outcome remains controversial. Aim of this study was to see the outcome of EVD in management of spontaneous IVH of brain assessing by Glasgow outcome scale (GOS) and modified Rankin scale (mRS) score compared with conservative management.Materials and Methods: Between July 2018 and June 2019, a consecutive 125 admitted patients with spontaneous IVH were enrolled in this quasi-experimental study. Among them 56 patient’s relative agreed to surgery who were accepted as case group and had EVDs. Remaining 69 patient’s relative declined authorization for surgery and were accepted as control group and underwent conservative management. Baseline demographics, clinical presentation, and hospital course, Glasgow coma scale score (GCS) for level of consciousness and modified Graeb score (mGS) for severity of ventricular haemorrhage were recorded at baseline and postoperatively. Admission Computed tomography (CT) scans performed within 24 hours of admission were reviewed for IVH type and hydrocephalus. Patients were followed up for 3 months post operatively and assessed using the GOS score and mRS score.Results: Both the groups were similar at baseline in terms of age (mean±SD: 59±14 vs 60±14, p = 0.645), sex and comorbidity distributions. However, patients who received EVDs had lower mean GCS score (p=